Friction mechanism in diamond-like carbon film sliding against various counterbodies. (November 2014) - Radhika, R.; Kumar, N.; Dash, S.; Ravindran, T. R.; Arivuolia, D.; Tyagi, A. K.
<x content-type="archive" xml:space="preserve">Abstract</x> In the present study, the tribological properties of hydrogenated diamond-like carbon (DLC) coating were investigated using various sliding counterbodies such as steel, Al2O3 and SiC balls. A friction mechanism based on surface chemistry and mechanical properties of sliding interfaces is proposed. During initial sliding passes, the high friction coefficient is governed by the surface roughness of the sliding interfaces. However, for longer sliding cycles, the sliding interfaces get smoothened and magnitude of friction coefficient is reduced. Under these experimental conditions, appropriate description of friction involves formation of carbonaceous transferlayer on ball sliding surface have been investigated.